2005
DOI: 10.1007/s00586-005-0893-7
|View full text |Cite
|
Sign up to set email alerts
|

Trunk muscular activation patterns and responses to transient force perturbation in persons with self-reported low back pain

Abstract: Trunk stability requires muscle stiffness associated with appropriate timing and magnitude of activation of muscles. Abnormality of muscle function has been implicated as possible cause or consequence of back pain. This experimental study compared trunk muscle activation and responses to transient force perturbations in persons with and without self-reported history of low back pain. The objective was to determine whether or not history of back pain was associated with (1) altered anticipatory preactivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…The trunk muscle preactivation level has been assessed only once in subjects with CLBP (Stokes et al 2006) and has been suggested as a potential confounding variable to be considered in future studies (Lee et al 2007). In partial agreement with the present results, Stokes et al (2006) showed a higher preactivation of back and abdominal muscles in subjects with CLBP than in controls.…”
Section: Assessment Of Potential Confounding Variablessupporting
confidence: 92%
See 1 more Smart Citation
“…The trunk muscle preactivation level has been assessed only once in subjects with CLBP (Stokes et al 2006) and has been suggested as a potential confounding variable to be considered in future studies (Lee et al 2007). In partial agreement with the present results, Stokes et al (2006) showed a higher preactivation of back and abdominal muscles in subjects with CLBP than in controls.…”
Section: Assessment Of Potential Confounding Variablessupporting
confidence: 92%
“…The trunk muscle preactivation level has been assessed only once in subjects with CLBP (Stokes et al 2006) and has been suggested as a potential confounding variable to be considered in future studies (Lee et al 2007). In partial agreement with the present results, Stokes et al (2006) showed a higher preactivation of back and abdominal muscles in subjects with CLBP than in controls. Unfortunately in that study, EMG signals were normalized with the use of maximal EMG obtained during MVCs, which might be questionable since it may artiWcially increase the estimated activation level if their subjects with CLBP had painrelated fears (Thomas et al 2008).…”
Section: Assessment Of Potential Confounding Variablessupporting
confidence: 92%
“…Participants with CLBP adopt a stiffening strategy to increase spine stability and to reduce the exacerbation of existing pain. 10,11 Thus, in our study, increased activity of latissimus dorsi could be due to pain severity (6 of 10 based on the data in Table 1) in patients with CLBP. According to the "pain-spasm-pain" theory, pain increases muscle activity and a vicious cycle of muscle spasm develops.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 It seems that increased activity of the trunk muscles can be due to abnormal motor recruitment patterns. 3 Stokes et al 10 reported that increased superficial trunk muscle activation was due to a "painadaptation" hypothesis. Participants with CLBP adopt a stiffening strategy to increase spine stability and to reduce the exacerbation of existing pain.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of muscle onset was based on the methods described by previous studies. 12,32 The onset of muscle activity was considered to occur if the average EMG amplitude every 20 milliseconds exceeded a threshold of 3 standard deviations above baseline for 20 milliseconds. A signal with baseline artifact was not determined as muscle onset, and we identified the onset with continually increased EMG signal from threshold values.…”
Section: Emg Analysismentioning
confidence: 99%